Rubrik Soeara Moehammadijah 1939-1942 - Saputro, M. Endy; Riowati, Eka (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
Soeara Moehammadijah, (later: Suara Muhammadiyah), has continuously become one of the longest living magazines in Indonesia. To date, the beginning of publication of Soeara Moehammadijah was published on 1915 and has progressively scattered information to the present day. Several dissertations have used this magazine for one of its main references. Several books have also examined how Muhammadiyah developed, either from education or da'wah, from this source. However, what is the actual content of this magazine, not many have studied it. This series presents the contents of the Soeara Moehammadijah column 1915 - 1940. This section presents the continuous sections of the rubric 1939 - 1942